1998
DOI: 10.1038/nm0598-575
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin-dependent kinase inhibitor p27Kip1 safeguards against inflammatory injury

Abstract: The cyclin-dependent kinase inhibitor p27Kip1 controls cell proliferation in response to normal mitogenic stimuli. We show here that p27Kip1 also safeguards against excessive cell proliferation in specific pathophysiologic settings. We used experimental glomerulonephritis as a paradigm for immune mediated inflammation and ureteral obstruction as a model for non-immune mediated inflammation. Renal function was substantially decreased in nephritic p27-/- mice compared with control mice, and this was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 25 publications
7
123
1
1
Order By: Relevance
“…p27 Ϫ/Ϫ mice exhibit multiple organ hyperplasia caused by generalized hypercellularity, which is most prominent between 4 to 8 weeks of age (Fero et al, 1996;Kiyokawa et al, 1996;Nakayama et al, 1996). p27 Ϫ/Ϫ mice also have an increased incidence of tumors, consistent with the body of evidence attributing a protective role to p27 in the progression and prognosis of proliferative diseases such as cancer (Catzavelos et al, 1997;Cordon-Cardo et al, 1998;Loda et al, 1997;Ophascharoensuk et al, 1998). These observations led to the hypothesis that the lack of p27 would enhance intimal proliferation after injury.…”
Section: Discussionmentioning
confidence: 56%
“…p27 Ϫ/Ϫ mice exhibit multiple organ hyperplasia caused by generalized hypercellularity, which is most prominent between 4 to 8 weeks of age (Fero et al, 1996;Kiyokawa et al, 1996;Nakayama et al, 1996). p27 Ϫ/Ϫ mice also have an increased incidence of tumors, consistent with the body of evidence attributing a protective role to p27 in the progression and prognosis of proliferative diseases such as cancer (Catzavelos et al, 1997;Cordon-Cardo et al, 1998;Loda et al, 1997;Ophascharoensuk et al, 1998). These observations led to the hypothesis that the lack of p27 would enhance intimal proliferation after injury.…”
Section: Discussionmentioning
confidence: 56%
“…Cells with increased CDK2 activity are more vulnerable to UV induced apoptosis and reducing CDK2 activity decreases apoptosis Previous studies have shown that apoptosis is increased in proliferating cell populations in certain forms of apoptosis (Danno and Horio, 1982;Nishioka and Welsh, 1994;Syljuasen and McBride, 1999) (Baker et al, 1994;Ophascharoensuk et al, 1998). However, the mechanisms linking these processes are not fully elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…The association of speci®c cyclin-CDKs and apoptosis has also been shown in vivo. Mice transgenic for both cyclin A and CDK2 show a greater incidence of apoptosis (Bortner and Rosenberg, 1995), and increased cyclin A-CDK2 activity coincides with a marked increase in apoptosis in in¯ammatory injury (Ophascharoensuk et al, 1998). Taken together, these studies demonstrate that speci®c cyclin-CDK complexes are involved in both the proliferative and apoptotic pathways following injury.…”
Section: Introductionmentioning
confidence: 98%
“…p27 has been shown to safeguard against excessive cell proliferation in experimental glomerulonephritis and ureteral obstruction (38). While p27 has beneficial effects in these specific pathophysiologic settings, it appears to play a detrimental role in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%